Sustainable Development Planning of Eco-Park Koto Katik Area in Padang Panjang City - Sukma Yudistira (Universitas Gadjah Mada, 2021)
Globally, ecotourism are struggling in implementing sustainable tourism principles. It is therefore important to identify source of challenges at planning process to avoid recurring problems in the future. Such a problema is apparent in the Koto Katik Ecopark in Padang Panjang, West Sumatera, despite government efforts utilizes the enormous opportunity for ecotourism development This paper evaluates the principles of sustainable tourism development adopted in the ecopark planning process. This research is based descriptive qualitative analysis data was collected through legal documents related to the planning process of Koto Katik Ecopark development. The data analysis includes description of the koto katik eco-park area, the potential for regional development, and examination of how sustainable tourism attributes exist. This study analyzes critical issues of ecotourism sustainable developmen, objectives, principles, and characteristics of the koto katik eco-park and their comparison with relevant theories and umtimately reveals the extent to which the principles of sustainable tourism development principles are followed. The result of the study shows that planning does not meet the principles of sustainable tourism development, such as the absence of conservation programs, design of tourism activities, distribution of stakeholder power, in planning, managing, and supervising ecotourism areas, analyzing the capabilities and expertise of local human resources, as well as supporting infrastructure and technology.